PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. HUTAMA KARYA (PERSERO) WILAYAH II PADA PEMASANGAN GIS 150 KV KALIBARU PT. PELINDO II DI JAKARTA - Saebani (Jurnal Pendidikan Teknik dan Vokasional, 2021)
Good and high employee performance can be achieved if all components of the company are integrated in a sustainable and good. The purpose and purpose of this study is to determine the effect of competence and work motivation on the performance of employees of PT. Hutama Karya (Persero) Region II on installation of GIS 150 kv Kalibaru PT. Pelindo II in Jakarta. To analyze and know about the influence of independent variable (competence and work motivation) on dependent variable (employee performance), then used correlation and regression test to know the most influential variable. Using simple random sampling (Simple Random Sampling), with 45 respondent samples of employees of PT. Hutama Karya (Persero) Region II on installation of GIS 150 kv Kalibaru PT. Pelindo II in Jakarta, while data processing using SPSS 16. From the results of tests that have been done, simultaneous regression test (F test) shows that all independent variables studied have a positive and significant effect on employee performance variables. Partial regression test (t test) shows that the competence variable has a positive and significant effect to employee performance variable. The magnitude of the effect caused by (Rsquare) by the variable of competence and mutual motivation toward the employee performance variable is 58,3%, while the rest 41,7% influenced by other variable not examined in this research. Keywords: competence, employee performance, work motivation